Good Corporate Governance dan Profitabilitas: Dampaknya terhadap Nilai Perusahaan di Bursa Efek Indonesia pada Perusahaan Sub Sektor Plastik dan Kemasan Yang Terdaftar di Bursa Efek Indonesia - Hasmirati Hasmirati; Alfin Akuba (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to find out and analyze how much influence good corporate governance and profitability have on company value in plastic and packaging sub-sector companies listed on the Indonesian Stock Exchange. The research is quantitative research. The analysis method uses multiple linear regression. The research results show that Good corporate governance does not significantly affect Company Value in Plastics and Packaging sub-sector companies listed on the Indonesia Stock Exchange because share ownership by management in plastics and packaging sub-sector companies is relatively low. Profitability significantly affects company value in the Plastics and Packaging sub-sector companies listed on the Indonesia Stock Exchange. This means that several companies in the plastics and packaging sub-sector have increased profits, followed by an increase in profits.